2022
DOI: 10.1101/2022.01.18.476786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection results in lasting and systemic perturbations post recovery

Abstract: SARS-CoV-2 has been found capable of inducing prolonged pathologies collectively referred to as Long-COVID. To better understand this biology, we compared the short- and long-term systemic responses in the golden hamster following either SARS-CoV-2 or influenza A virus (IAV) infection. While SARS-CoV-2 exceeded IAV in its capacity to cause injury to the lung and kidney, the most significant changes were observed in the olfactory bulb (OB) and olfactory epithelium (OE) where inflammation was visible beyond one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 100 publications
(152 reference statements)
6
24
0
Order By: Relevance
“…Our study reveals that there are differences in the neuroinvasiveness and neurovirulence among the ancestral D614G and the Delta and Omicron BA.1 SARS-CoV-2 variants in the hamster model in the acute phase of the infection. D614G appears to be neuroinvasive, entering the CNS via the olfactory nerve, as previously observed in other studies (Frere et al, 2022; Imai et al, 2020; de Melo et al, 2021; Zazhytska et al, 2022). In contrast, although viral RNA was detected in the olfactory bulbs by RT-qPCR in Delta and Omicron BA.1 inoculated hamsters, this could not be confirmed by the detection of viral proteins or RNA by IHC and ISH respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Our study reveals that there are differences in the neuroinvasiveness and neurovirulence among the ancestral D614G and the Delta and Omicron BA.1 SARS-CoV-2 variants in the hamster model in the acute phase of the infection. D614G appears to be neuroinvasive, entering the CNS via the olfactory nerve, as previously observed in other studies (Frere et al, 2022; Imai et al, 2020; de Melo et al, 2021; Zazhytska et al, 2022). In contrast, although viral RNA was detected in the olfactory bulbs by RT-qPCR in Delta and Omicron BA.1 inoculated hamsters, this could not be confirmed by the detection of viral proteins or RNA by IHC and ISH respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Long-term deficits in nuclear architecture could be applicable to other neuronal populations since adult CNS neurons also assemble long-range cis and trans genomic compartments between OR genes and other neuronal gene families (Jiang et al, 2017;Tan et al, 2021). Additional mechanisms, such as sustained expression of antiviral programs (Frere et al, 2022), damage in tissue vasculature, and hypoxia (Thakur et al, 2021), could also contribute to long-lasting neurological deficits, including the loss of smell (Lane et al, 2010). In either case, the realization that the sense of smell relies on extremely ''fragile'' genomic interactions between chromosomes has important implications: if OR expression ceases every time maladaptive physiological responses disrupt interchromosomal OR contacts, then olfaction may act as the ''canary in the coal mine'' for a variety of human conditions, from viral infections to neurodegeneration (Albers et al, 2006).…”
Section: Comparing the Effects Of Sars-cov-2 Infection In Hamster And...mentioning
confidence: 99%
“…The route of virus entry into the CNS likely influences disease manifestation. For example, Bell's palsy, which some studies have suggested to be associated with SARS-CoV-2 infection, could be the result of virus invasion via the facial nerve [34]; virus infection along the olfactory nerve could result in anosmia [16][17][18]35]; and spread to the CNS via viremia and/or infection of brain microvascular endothelial cells may result in intracerebral hemorrhage [36,37]. Whether each of these infection routes is directly associated with specific disease manifestation requires more in-depth studies.…”
Section: Trends Trends In In Neurosciences Neurosciencesmentioning
confidence: 99%
“…Anosmia has often been associated with SARS-CoV-2 infection, at least with the initial variants of the virus, but the underlying pathology is not fully understood. The mechanisms underlying olfactory dysfunction may involve a complex and possibly long-lasting interplay of dysregulated immune responses in the olfactory mucosa and the olfactory bulb, as well as virus-induced lesions along the olfactory tract [18,35]. In hamsters and mice, there is evidence for focal destruction of the olfactory mucosa, associated with an influx of inflammatory cells [19].…”
Section: Neurovirulencementioning
confidence: 99%
See 1 more Smart Citation